2019
DOI: 10.1002/ange.201908758
|View full text |Cite
|
Sign up to set email alerts
|

HfN Nanoparticles: An Unexplored Catalyst for the Electrocatalytic Oxygen Evolution Reaction

Abstract: Water electrolysis is one of the most promising methods to produce H 2 and O 2 as high potential fuels.Comparing the two half-reactions,the oxygen evolution reaction (OER) is the more difficult to be optimizedand still relies on expensive noble metal-based catalysts such as Ru or Ir.Inthis paper,we prepared nanoparticles of HfN and Hf 2 ON 2 and tested them for the OER for the first time.The HfN sample,i np articular, showed the highest activity,requiring an overpotential of only 358 mV at 10 mA cm À2 in Fe-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…It can be further concluded that the synergy of spheres and rods provided efficient electrocatalysts with superior stability and promising activity. As mentioned before, Hf nanoparticles have been recently reported as a novel electrocatalyst with relatively low values of overpotential at 10 mAcm −2 (358 mV) and Tafel slope of 85 mV/dec [ 5 ]. Therefore, it is desired to study these materials in greater detail and various morphology to reveal a clear correlation between spinels shape and their electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be further concluded that the synergy of spheres and rods provided efficient electrocatalysts with superior stability and promising activity. As mentioned before, Hf nanoparticles have been recently reported as a novel electrocatalyst with relatively low values of overpotential at 10 mAcm −2 (358 mV) and Tafel slope of 85 mV/dec [ 5 ]. Therefore, it is desired to study these materials in greater detail and various morphology to reveal a clear correlation between spinels shape and their electrochemical performance.…”
Section: Resultsmentioning
confidence: 99%
“…The choice is mostly between noble metal and their oxides such as Pt, Ru, RuO 2 , Ir, IrO 2 . Furthermore, it is worth mentioning that Giordano et al have recently reported Hf nanoparticles for OER, which exhibiting interesting performance and low over-potential [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the combination of nitrogen atoms in graphite structure, nitrogen-doped carbon materials can perform impressive ORR catalytic activity. In addition, Defilippi et al [82] took advantage of the sol-gel technique and successfully synthesized HfN NPs (less than 15 nm in diameter), which exhibited a quite low overpotential of 358 mV at 10 mA•cm -2 and long term stability as an OER electrocatalyst. This recent study indicates that metal nitrides possess high conductivity, stability, and melting point, and these properties make them qualified to be active both for ORR and OER.…”
Section: Iron Carbidementioning
confidence: 99%
“…"High entropy" was firstly proposed by Cantor et al 7 and Yeh et al 8 in alloys, meanwhile, this concept has been extended to high entropy oxides, 4 high entropy carbides, 5 high entropy borides, 9 high entropy nitrides (HENs), [10][11][12] and so on. 13,14 Metal nitrides are kinds of metal compounds constructed by metal-nitrogen covalent bonds, which have attracted great attention due to their unique features, [15][16][17] such as high chemical stability, excellent physical properties, and diverse electrical characteristics. Likewise, some applications such as energy-storage, 11 wear-resistant coatings, [18][19][20] diffusion barriers for microelectronics 21,22 are achieved from HENs.…”
Section: Introductionmentioning
confidence: 99%